Sustainability in higher education: Comparison of the Asia-Pacific region and Serbia - Đukić Gordana; Ilić Biljana (Trendovi u Poslovanju, 2020)
Mankind is slowly and painfully realizing that sustainability is very complicated in the current patterns of human lives. The fact that a billion times smaller enemy (virus) can put all the achievements of the previous civilization to the test testifies to how powerless man is before nature. Regardless of environmental and humanitarian problems, there is hope that man will be able to react in the right way, with a greater understanding of the dynamics of natural and social processes. So, to survive, it is necessary to expand knowledge, it is necessary to find the right path to sustainability. Dissemination of knowledge helps to raise the environmental awareness of man, and it is necessary at the very beginning of the education of each individual, to introduce knowledge about sustainable development and the ways of the same. With the maturation of the individual, knowledge needs to be increased until the moment when the person himself decides on higher education. The paper represents a modest contribution to achieving the path of sustainability, pointing out the importance of education in higher education institutions with the aim of understanding the importance of how inseparable man is from nature and how much he depends on it. Therefore, the authors present the practice of higher education from the countries of the Asia-Pacific region, aimed at understanding the importance of higher education for sustainable development. The authors will refer to Higher Education in Serbia as well as how the understanding of sustainability in education is encouraged.